How urban spaces remember: Memory and transformation at two expo sites - Minner, Jennifer; Abbott, Martin (International Planning History Society Proceedings, 2018)
International Expos can leave long-lasting imprints on host cities. The production and evolution of legacy public spaces from these events deserve scholarly attention. Case studies were conducted at two former expo sites in the US and Australia, focusing on the role of retention, reuse, heritage, and parks conservation in the evolution of public spaces. In preparation for Hemisfair ’68, in San Antonio, Texas, conservationists saved 22 historic buildings out of hundreds demolished. Although only a small proportion of buildings were preserved, preservationists challenged a modernist urban renewal plan and the design became a precedent for incorporating heritage conservation in modern urban design. Today, the Hemisfair site is subject to new redevelopment plans. Calls to preserve remaining modernist pavilions challenge New Urbanist visions for the site. In a second case study, an industrial district was cleared and a working-class neighbourhood transformed for Expo ’88, in Brisbane, Queensland. The site was later redeveloped into the South Bank Parklands. Over time, South Bank evolved through redevelopment and master planning, public outcry, and instances of conservation in and around the expo site. Common to both cases is the conservation of parks, heritage, and artwork, outcomes of individual and collective actions to shape urban landscapes.